2006
DOI: 10.1017/s031716710000528x
|View full text |Cite
|
Sign up to set email alerts
|

Immunizations and Autism: A Review of the Literature

Abstract: ABSTRACT:Because of a temporal correlation between the first notable signs and symptoms of autism and the routine childhood vaccination schedule, many parents have become increasingly concerned regarding the possible etiologic role vaccines may play in the development of autism. In particular, some have suggested an association between the Measles-Mumps-Rubella vaccine and autism. Our literature review found very few studies supporting this theory, with the overwhelming majority showing no causal association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 46 publications
(41 reference statements)
2
46
0
2
Order By: Relevance
“…Some chemtrails conspirators take the increased number of articles on the subject itself as evidence that there must be something to their theory. This mirrors what we can observe with those arguing against vaccinating children, often for unwarranted fears of a link between vaccinations and autism (Doja and Roberts, 2006;Miller and Reynolds, 2009). Much like 'anti-vaxxers' are hardly persuaded by evidence against their theory, chemtrails conspirators, too, are apparent masters in picking 'evidence' to support their views, while ignoring evidence against them.…”
supporting
confidence: 70%
“…Some chemtrails conspirators take the increased number of articles on the subject itself as evidence that there must be something to their theory. This mirrors what we can observe with those arguing against vaccinating children, often for unwarranted fears of a link between vaccinations and autism (Doja and Roberts, 2006;Miller and Reynolds, 2009). Much like 'anti-vaxxers' are hardly persuaded by evidence against their theory, chemtrails conspirators, too, are apparent masters in picking 'evidence' to support their views, while ignoring evidence against them.…”
supporting
confidence: 70%
“…In all cases it was noted by the Court of Federal Claims, or indicated in settlement agreements, that the children had autism or ASD [39]. On the other hand, numerous epidemiological studies have found no association between receipt of selected vaccines (in particular the combined measles, mumps, and rubella vaccine) and autism [10,[40][41][42][43][44][45], and there is no accepted mechanism by which vaccines could induce autism [46].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the overwhelming benefits reported for most vaccines, concerns are raised from time to time linking immunizations to different conditions such as autism [2] and autoimmune disorders [3] such as multiple sclerosis (MS) [4]. Unfortunately, in many cases, these studies are merely case reports, poorly designed observational studies, or welldesigned studies with a small number of participants from which valid conclusions cannot be drawn.…”
Section: Introductionmentioning
confidence: 99%